In Brucella: Selective pressure may turn some genes on instead of default off position. (June 2017) - Wareth, Gamal; Melzer, Falk; Neubauer, Heinrich
Abstract: Brucellosis is a major zoonosis with worldwide prevalence; more than half a million new human cases are expected every year. The genus Brucella (B) encompasses 12 accepted nomo-species and brucellae were described as Gram negative, aerobic, non-motile and non-haemolytic facultative intracellular bacteria. The Brucella genome contains flagella-specific genes and various hemolysins, but no flagella are formed and nor hemolysis is seen. Selective pressure can cause accumulation of mutations that turn those genes on instead of default off position and provoked the motile and hemolytic phenotypes. The ability of brucellae to change from a non-haemolytic to a haemolytic phenotype might influence their pathogenicity and could provide a substantial insight to explain the correlation of acute brucellosis and hemolytic anemia in humans.